Prognostic biomarker MCP-4 triggers epithelial-mesenchymal transition via the p38 MAPK pathway in ovarian cancer - Li, Siting; Hu, Yuexin; Liu, Ouxuan; Li, Xiao; Lin, Bei (Frontiers in Oncology, 2022)
Background Monocyte chemoattractant protein-4 (MCP-4/CCL13) is a proinflammatory factor that is overexpressed in various malignant tumors and may play an important role in tumor progression and metastasis. However, its role and mechanism of action in ovarian cancer remains unknown. Methods Immunohistochemistry (IHC) was performed to detect the expression of MCP-4 in ovarian cancer tissues, and the effect of MCP-4 on patient survival and prognosis was analyzed. Overexpression and suppression of MCP-4 in ovarian cancer cell lines were then established, and their effects on cell invasion, migration, and apoptosis were studied. ES-2 cell lines were employed to establish a peritoneal dissemination model in nude mice. Western blotting was performed to detect the expression of epithelial mesenchymal transition (EMT) markers and the p38 mitogen-activated protein kinase (p38 MAPK) signaling pathway. Results MCP-4 was highly expressed in ovarian cancer tissues and its expression level was related to the prognosis of patients with ovarian cancer. MCP-4 overexpression promoted the migration and invasion of ovarian cancer cells but inhibited apoptosis. MCP-4 overexpression increased the expression of MMP-2, MMP-9, N-cadherin, vimentin and Bcl2/Bax and decreased the expression of E-cadherin. MCP-4 overexpression increased the phosphorylation of the p38 MAPK pathway. The inhibition of MCP-4 expression indicated an opposite trend. In vivo experiments have also confirmed that MCP-4 overexpression can promote metastasis of ovarian cancer. Conclusion MCP-4 promotes ovarian cancer progression through the p38 MAPK signaling pathway, and may be a potential biomarker and therapeutic target for ovarian cancer.